LARYNX DISEASES - Yu.L. Soldatskiy (Педиатрическая фармакология, 2008)
In this article, the author continues to introduce laryngopathy to pediatricians, namely diseases with acute inflammatory diseases and acute stenoses. Traditionally, large attention is paid not only to the treatment of the pathological often life menacing conditions but also to the pathogenesis and clinical implications.Key words: acute laryngitis, acute allergic laryngeal edema, acute epiglottitis, aspiration, pathogenesis, clinical course, treatment, children.